2020
DOI: 10.1007/s00261-020-02805-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of liver-to-spleen ratio, lung CT scores, clinical, and laboratory findings of COVID-19 patients with two consecutive CT scans

Abstract: Purpose Given the lack of information about abdominal imaging findings and correlation with clinical features of COVID-19, we aimed to evaluate the changes in hepatic attenuation during the course of disease. Our aim was to correlate the liverto-spleen ratio (L/S), clinical, laboratory findings, and lung CT scores of patients with COVID-19 who had two consecutive chest CTs. Methods A retrospective search was performed between March 1, 2020 and April 26, 2020 to identify patients who had positive RT-PCR tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
12
2
2
Order By: Relevance
“…In their study, P. [15]. However, our data show no statistically significant differences between the rate of liver density changes across the groups and the development of pneumonia of varying degrees.…”
Section: Discussioncontrasting
confidence: 72%
“…In their study, P. [15]. However, our data show no statistically significant differences between the rate of liver density changes across the groups and the development of pneumonia of varying degrees.…”
Section: Discussioncontrasting
confidence: 72%
“…Concerning liver injury in COVID-19, immune-mediated damage as a result of the severe inflammatory response following SARS-CoV-2 infection [20] , direct cytotoxicities as a result of active viral replication in hepatic cells [21] , and anoxia [22] are thought to be involved. A previous report showed that L/S was reduced in cases that led to severe disease than in those that did not [23] . Therefore, it is possible that a decreased L/S indirectly reflects that hepatic steatosis and mild lobular and portal inflammation result from liver damage due to the above.…”
Section: Discussionmentioning
confidence: 85%
“…There are some studies examining the relationship between COVID-19 severity and liver density and damage, and detecting a decrease in density and an increase in liver damage in severe/ progressive disease. 6,21,[34][35][36][37][38] Guler et al 21 found no significant difference in mean L/S values at admission to hospital, but the L/S value was significantly lower in the progressive group at follow-up. In group comparisons, there was a significant decrease in L/S values on the follow-up CT in the progressive group.…”
Section: Discussionmentioning
confidence: 99%